Insights on the NF-κB System Using Live Cell Imaging: Recent Developments and Future Perspectives - Kizilirmak, Cise; Bianchi, Marco E.; Zambrano, Samuel (Frontiers in Immunology, 2022)
The transcription factor family of nuclear factor kappa B (NF-𝜅B) proteins is widely recognized as a key player in inflammation and the immune responses, where it plays a fundamental role in translating external inflammatory cues into precise transcriptional programs including the timely expression of a wide variety of cytokines/chemokines. Live cell imaging in single cells showed approximately 15 years ago that the canonical activation of NF-𝜅B upon stimulus is very dynamic, including oscillations of its nuclear localization with a period close to 1.5 hours. This observation has triggered a fruitful interdisciplinary research line that has provided novel insights on the NF-𝜅B system: how its heterogeneous response differs between cell types but also within homogeneous populations; how NF-𝜅B dynamics translate external cues into intracellular signals and how NF-𝜅B dynamics affects gene expression. Here we review the main features of this live cell imaging centered approach to the study of NF-𝜅B, highlighting the key findings, the existing gaps of knowledge and hinting towards some of the potential future steps of this thriving research field.